Effect of Long-Term Exercise on Liver Lipid Metabolism in Chinese Patients With NAFLD: A Systematic Review and Meta-Analysis - Gao, Ye; Lu, Jiandong; Liu, Xinhong; Liu, Jingqi; Ma, Qirui; Shi, Yajun; Su, Hao (Frontiers in Physiology, 2021)
Purpose: Using meta-analysis to evaluate the effect of various long-term exercises (more than 4 weeks) on liver lipid metabolism of Chinese patients with non-alcoholic fatty liver disease (NAFLD) and provides more targeted exercise recommendations. Methods: Four databases consisting of PubMed, Web of Science, China Science and Technology Journal Database (VIP), China Knowledge Resource Integrated Database (CNKI) were searched up to May 2021. Randomized controlled trials (RCTs) were eligible, and the outcomes of body composition, lipid metabolism (including triglyceride (TG), total cholesterol (TC), low-density lipoprotein-cholesterol (LDL-C) and high-density lipoprotein-cholesterol (HDL-C)), and liver function (including Alanine aminotransferase (ALT) and Aspartate aminotransferase (AST)) were used to assess the effectiveness of long-term exercise on Chinese patients with NAFLD. Results: 11 articles with a total of 13 data points (involving 1006 participants) satisfied the inclusion criteria and were pooled in the meta-analysis. The findings demonstrated that long-term exercise decreased the level of triglyceride (TG) [-0.50, 95%CI(-0.64, -0.36], total cholesterol (TC) [-0.55, 95%CI(-0.92, -0.18)], Low Density Lipoprotein-Cholesterol (LDL-C) [-0.29, 95%CI(-0.43, -0.15)], Alanine aminotransferase (ALT) [-3.45, 95%CI(-6.78, -0.12)], Aspartate aminotransferase (AST) [-6.91, 95%CI(-10.00, -3.81)], and Body Mass Index (BMI) of patients who did exercise last more than six months [-1.55, 95%CI(-2.32, -0.79)] significantly. The effect on high-density lipoprotein cholesterol (HDL-C) was not obvious. Conclusion: Long-term exercise can improve the levels of TG, TC, LDL-C, ALT, AST in Chinese patients with NAFLD significantly, and exercise last more than six months can decrease the BMI of Chinese patients with NAFLD.